Foliar Delivery of siRNA Particles for Treating Viral Infections in Agricultural Grapevines. (10th July 2021) - Avital, Aviram; Muzika, Noy Sadot; Persky, Zohar; Bar, Gili; Michaeli, Yuval; Fridman, Yulia; Karny, Avishai; Shklover, Jeny; Shainsky, Janna; Savaldi‐Goldstein, Sigal; Weissman, Haim; Shoseyov, Oded; et al.
Abstract: Grapevine leafroll disease (GLD) is a globally spreading viral infection that causes major economic losses by reducing crop yield, plant longevity, and berry quality, with no effective treatment. Grapevine leafroll associated virus‐3 (GLRaV‐3) is the most severe, prevalent GLD strain affecting wine production. Here, the ability of RNA interference (RNAi), a non‐GMO gene‐silencing pathway, to treat GLRaV‐3 in infected Cabernet Sauvignon grapevines is evaluated. Lipid‐modified polyethylenimine (lmPEI) is synthesized as the carrier for long double‐stranded RNA (dsRNA, 250‐bp‐long) that targets RNA polymerase and coat protein is a gene target that are conserved in the GLRaV‐3 genome. Self‐assembled dsRNA–lmPEI particles, 220 nm in diameter, display inner ordered domains spaced 7.3 ± 2 nm from one another, correlating to lmPEI wrapping spirally around the dsRNA. The particles effectively protect RNA from degradation by ribonucleases and show to increase uptake rate into plant cells as a result of the lipid component comprising the RNA carrier. In three field experiments, a single dose of foliar sprayed treatment of the RNA‐particles knocks down GLRaV‐3 titer, and multiple doses of the treatment keep the viral titer at baseline and trigger recovery of the vine and berries. This study demonstrates RNAi as a promising platform for treating viral diseases in agriculture. Abstract : Viral infections pose a great threat to global farming and wine production. Using 200 nm dsRNA lipid‐particles, it is possible to downregulate the viral titer in cabernet sauvignon vineyards to healthy levels. This study provides insights into the synthesis and application of RNA formulations in agriculture.